Learning Curve Based Sigma Level Determination in Interrupted Non-Production Processes - Molnár, Viktor; Metszosy, Gabriella (International Journal of Engineering and Management Sciences, 2018)
The philosophy and methods of six sigma process development have been applied successfully since mid1980s, and the application of the six sigma concept in non-production processes has increased significantly in the last decade. In this paper processes that can be characterized by learning curves are modeled. The quality of such processes can be analyzed on the basis of the six sigma concept. In this paper two back office processes are analyzed. The processes are built up of simple repeated steps and incorporate some interruptions. The application of the model allows the calculation of the maximally permitted number of interruptions in the process if the preliminary determined norm is to be kept.